Cloning, heterologous expression and characterisation of a recombinant cellobiohydrolase from Humicola insolens ATCC16454 in Pichia pastoris - Amatul Samahah Md Ali,; Farah Diba Abu Bakar,; Rosli Md Illias,; Osman Hassan,; Abdul Munir Abdul Murad, (Malaysian Society of Applied Biology, 2015)
A cellobiohydrolase gene from the thermophilic fungus Humicola insolens ATCC 16454 was expressed in the methylotrophic yeast Pichia pastoris X-33, and the biochemical properties of the recombinant protein were characterised. The full-length cDNA of the cellobiohydrolase gene avi2 was cloned into the P. pastoris expression vector pPICZαC and expressed extracellularly as a recombinant cellobiohydrolase protein with a molecular weight of approximately 52.3 kDa. The purified recombinant Avi2 enzyme displayed an optimal activity at 50°C and was found stable between temperatures of 30°C and 60°C. The optimal pH of the enzyme was pH 5.0. More than 80% of the enzyme activity was retained at pH values ranging from pH3.0 to pH9.0. Recombinant Avi2 enzyme showed its highest activity towards the substrates Avicel (0.075 U mg-1) and Sigmacell-cellulose (0.018 U mg-1). Very low or undetectable hydrolysis was observed with cellobiose and filter paper. Metal ions, such as Mn2+, Co2+, and Ba2+, increased the activity of the recombinant enzyme. Manganese ions caused the highest increase in activity of approximately 1.38-fold compared to the control assay. Other ions such as Pd2+, Cu2+, Zn2+, Fe2+, and SDS, however, inhibited Avi2 enzyme activity. Interestingly, this recombinant enzyme showed high pH stability when it was incubated in either acidic or basic solutions.